Modern motherhood and the medicalization of childbirth in the pages of the Boletim da Legiao Brasileira de Assistencia, 1945-1964 - Mariante da Silva, Bruno Sanches [UNESP] (Fundaco Oswaldo Cruz, 2018)
Between 1945 and 1964, Brazil underwent an accelerated process of modernization. Increasingly urbanized and guided by the precepts of social hygiene, the country was keen to refute any practices or customs regarded as traditional or old-fashioned. As such, the traditional figure of the midwife was supplanted by medical knowledge, which came to exert influence on childbirth and motherhood. This text analyzes Boletim da LBA, investigating the medicalization and scientification of childbirth and motherhood and focusing on the scientific and moral clashes about motherhood and childbirth contained in this, the official publication of the country's largest welfare institution.
Keywords: motherhood; modernity; Legiao Brasileira de Assistencia; painless childbirth; hospital birth